The role of ascitic fluid viscosity in the differential diagnosis of ascites - Gokturk, Huseyin Savas (Pulsus Group Inc, 2010)
BACKGROUND: Ascites is defined as the pathological accumulation of fluid in the peritoneal cavity. It is the most common complication of cirrhosis, which is also the most common cause of ascites. Viscosity is a measure of the resistance of a fluid to deform under shear stress. Plasma viscosity is influenced by the concentration of plasma proteins and lipoproteins, with the major contribution from fibrinogen. To our knowledge, the viscosity of ascitic fluid has not yet been studied. OBJECTIVE: To evaluate the role of ascitic fluid viscosity in discriminating between ascites due to portal hypertension-related and nonportal hypertension-related causes, and to compare results with the serum-ascites albumin gradient (SAAG). METHODS: The present study involved 142 patients with ascites presenting with diverse medical problems. Serum total protein, albumin, glucose, lactate dehydrogenase (LDH) levels and complete blood count were obtained for all subjects. Paracentesis was performed routinely on admission and all ascitic fluid samples were evaluated by manual cell count with differential, ascitic fluid culture and biochemistry (total protein, albumin, glucose and LDH). Cultures of ascitic fluid were performed at bedside in all patients using blood culture bottles. Ascitic fluid viscosity was measured in a commercially available cone and plate viscometer. RESULTS: Of the 142 patients studied, 34 (24%) had an SAAG of 11 g/L or less, whereas 108 (76%) had an SAAG of greater than 11 g/L. Sex and mean age did not differ significantly between the two groups (P>0.05). Serum total protein, albumin, glucose, LDH levels, leukocyte count, ascitic fluid glucose levels and ascitic fluid leukocyte counts were similar in both groups, with no statistically significant relationship detected (P>0.05). However, the mean (±SD) ascitic fluid total protein (0.0172±0.1104 g/L versus 0.043±0.011 g/L), albumin (0.0104±0.0064 g/L versus 0.0276±0.0069 g/L) and LDH (102.76±80.95 U/L versus 885.71±199.93 U/L) were found to be higher in patients with an SAAG of 11 g/L or less than in those with an SAAG of greater than 11 g/L (P<0.001). The mean ascitic fluid viscosities were 0.86±0.12 centipoise (cP) and 1.22±0.25 cP in patients with an SAAG greater than 11 g/L and an SAAG of 11 g/L or less, respectively (P<0.001). Although ascitic fluid infection was detected in 35 patients (24.6%) (19 patients with spontaneous bacterial peritonitis, seven patients with culture-negative neutrocytic ascites, three patients with monobacterial non-neutrocytic bacterascites and six patients with secondary bacterial peritonitis), no significant effect on ascitic fluid viscosity was detected. Multiple linear regression analysis revealed that ascitic fluid total protein, albumin and LDH levels were independent predictors of ascitic fluid viscosity (P<0.001). The sensitivity, specificity, and positive and negative predictive values of ascitic fluid viscosity for the discrimination between ascites due to portal hypertension-related and nonportal hypertension-related causes according to the SAAG were determined by receiver operating characteristic analysis. Regarding the cut-off value of 1.03 cP, ascitic fluid viscosity measurement had a high sensitivity, specificity (98% and 80%, respectively), and positive and negative predictive value (79% and 94%, respectively) for the etiological discrimination of ascites. CONCLUSION: The measurement of ascitic fluid viscosity correlates significantly with SAAG values. In view of its simplicity, low cost, small sample volume requirement and allowance for measurement in previously frozen samples, measurement of ascites viscosity could be useful for the accurate and rapid classification of ascites.